From the Synthesis of Biobased Cyclic Carbonate to Polyhydroxyurethanes: A Promising Route towards Renewable Non‐Isocyanate Polyurethanes. Issue 15 (26th June 2019) - Carré, Camille; Ecochard, Yvan; Caillol, Sylvain; Avérous, Luc
Abstract: With a global production of around 18 million tons (6th among all polymers) and a wide range of applications, such as rigid and soft foams, elastomers, coatings, and adhesives, polyurethanes (PUs) are a major polymer family. Nevertheless, they present important environmental and health issues. Recently, new and safer PUs, called non‐isocyanate polyurethanes (NIPUs), have become a promising alternative to replace conventional PUs. Sustainable routes towards NIPUs are discussed herein from the perspective of green chemistry. The main focus is on the reaction between biobased carbonates and amines, which offers an interesting pathway to renewable polyhydroxyurethanes (PHUs). An overview of different routes for the synthesis of PHUs draws attention to the green synthesis of cyclic carbonate (CC) compounds and the aminolysis reaction. Current state‐of‐the‐art of different biobased building blocks for the synthesis of PHUs focuses on CC compounds. Three classes of compounds are defined according to the feedstock: 1) vegetable fats and oils, 2) starch and sugar resources, and 3) wood derivatives. Finally, biobased PHU properties are discussed. Abstract : Going full circle : Polyhydroxyurethanes, for the preparation of non‐isocyanate polyurethanes, are the best candidate to replace polyurethanes. This Review focuses on sustainable ways to synthesize cyclocarbonates from renewable resources. Different parameters that affect the aminolysis reaction and properties of the resulting materials are also discussed.